2020
DOI: 10.3390/su12124999
|View full text |Cite
|
Sign up to set email alerts
|

Linking Household Food Security and Food Value Chains in North West Mt. Kenya

Abstract: Smallholder farmers and pastoralists produce the largest proportion of food consumed in sub-Saharan Africa. However, they remain among the food insecure populations. This paper explores the food (in)security among smallholder farmers and pastoralists using a sample of 175 households in three agro-food value chains of wheat, dairy, and beef in the north-west Mt. Kenya region. The study seeks to answer if a farmer’s participation in a particular agro-food value chain determines his/her food security situation. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
(23 reference statements)
2
6
0
Order By: Relevance
“…Moreover, farmers groups also allow members to share their experiences among farmers and other existing groups. This result is consistent with several earlier studies conducted in Zambia, and Kenya [24,33]. This finding suggested that supporting farmers' association and the empowerment of existing formal and informal groups, mainly through mobilizing of community, should be encouraged by government and private organizations.…”
Section: Factors Affecting Household Food Insecurity Prevalencesupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, farmers groups also allow members to share their experiences among farmers and other existing groups. This result is consistent with several earlier studies conducted in Zambia, and Kenya [24,33]. This finding suggested that supporting farmers' association and the empowerment of existing formal and informal groups, mainly through mobilizing of community, should be encouraged by government and private organizations.…”
Section: Factors Affecting Household Food Insecurity Prevalencesupporting
confidence: 92%
“…The severity of food insecurity and vulnerability of farming households mostly depends on poor agricultural practice [13,14]. Farming households have significant potential to increase food security by ensuring the accessibility of food through production, decreasing food costs through an increased food supply, and generating income [24]. However, Afghanistan faces problems in reaching food security: their production remains low and hampered by several elements such as a lack of agricultural inputs, credit access, extension service, farmer organization, and market access [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an indication that smallholders may have the possibility to benefit as such from economies of scale by being organized in groups. Studies (Thomas et al, 2011;Fischer and Qaim, 2014;Mukhovi et al, 2020;Mwangi et al, 2020) have shown that smallholder farmers in developing countries like Kenya obtain economic and social benefits such as improved access to markets and market-related services, credit, information and training from group membership. With the devolution of agriculture in Kenya, we advocate for county-level government support to strengthen farmer groups.…”
Section: Discussionmentioning
confidence: 99%
“…Sub-Saharan Africa is the only region in the world where more than one-third of the population suffers from widespread hunger, and smallholder farmers, who produce more than 80% of Africa's food, face caloric and micronutrient deficiencies [76]. South Africa and Kenya are representative of the region, where 61% of households suffer from mild, moderate, or severe food insecurity [77]. Studies from this region study focused primarily on smallholder farmers.…”
Section: Authorsmentioning
confidence: 99%